Analisis Penyebab Kecelakaan Kerja Dengan Menggunakan Metode Analytic Hierarchy Process (AHP) di PT BSPL - Eka Sulistyaningsih; Adi Nugroho (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
A work accident can be defined as any unsafe act or condition that can result in a loss. Accidents caused by human actions that do not meet safety are called unsafe human actions. Meanwhile, accidents caused by unsafe environmental conditions are called unsafe conditions. The risk of work accidents is a major concern in the company. This is caused by the consequences that occur in work accidents to the deadly consequences of these accidents. This makes risk analysis even more important. One method that is relevant and has a consistency value calculation in analyzing the faktors that cause work accidents at PT. BSPL is the AHP method. Based on calculations using the AHP method, the main factor of work accidents at PT. BSPL is the human factor. This is in accordance with field observations, namely the lack of supervision from the company on the K3 culture for employees and some employees do not use complete PPE when working. To overcome the factors of work accidents that occurred at PT. BSPL, what companies need to do is improve the human factor mindset. Keeping workers safe at work and conducting OHS training.